Model pembelajaran Scramble dalam Meningkatkan Keterampilan Membaca Pemahaman Siswa SD - M. Hafiz Fathony; Asni Deselia Khairunnisa; Marlina (FKIP, Universitas Palangka Raya, 2025)
Students' understanding of reading is still low which is characterized by reading comprehension results below the criteria completeness, lack of interest in reading, not being able to determine the main idea and make conclusions appropriately and reading competence that is not optimal occurs in grade IV students of SDN Benua Riam. This study aims to improve the reading comprehension skills of fourth grade students of SDN Benua Riam through the Scramble learning model. This research is a collaborative Classroom Action Research carried out in two cycles with reference to the Kemmis and Taggart model, which includes the stages of planning, implementation, observation, and reflection. The research subjects were 18 fourth grade students. Data were collected through observation, interviews, documentation, and learning outcome tests according to reading comprehension indicators, which were analyzed quantitatively and qualitatively. The results showed that the Scramble learning model can improve students' reading comprehension learning outcomes. Teacher activities increased and met the success indicator of 92% with very good criteria. Students' activities increased and met the success indicator of 86% with very active criteria. Students' learning completeness increased from 39% in the first cycle and meeting to 83.3% at the end of cycle II. This increase shows that the use of the Scramble learning model can create fun learning, increase student participation, and improve student learning.